2023
DOI: 10.1101/2023.09.11.557250
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Biological and Genetic Determinants of Glycolysis: Phosphofructokinase Isoforms Boost Energy Status of Stored Red Blood Cells and Transfusion Outcomes

Travis Nemkov,
Daniel Stephenson,
Eric J. Earley
et al.

Abstract: Glycolysis is a central metabolic pathway in health and disease,1an essential one in mature red blood cells (RBCs), which rely on the Embden-Meyerhof-Parnas pathway, i.e., glycolysis, as the sole source of energy generation.2During aging in vivo and in vitro under blood bank conditions,3the adenosine triphosphate (ATP) generated via glycolysis in mitochondria-devoid mature RBCs is essential for the modulation of oxygen kinetics,4deformability2and, ultimately, intra- and extra-vascular hemolysis.3Here we draw u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
2

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 142 publications
0
5
0
Order By: Relevance
“…RBCs are well known for their near exclusive reliance on glycolysis for the generation of ATP, the pentose phosphate pathway for NADPH regeneration, and the purine salvage pathway for maintaining adequate nucleotide concentrations. Many of these rate-limiting enzymes are pH sensitive, including hexokinase ( HK1 ), phosphofructokinase isozymes ( PFKL , PFKM , PFKP )[102], and G6PD . The product of glycolysis in RBCs is lactate [31], which exists in equilibrium with lactic acid at physiological pH.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…RBCs are well known for their near exclusive reliance on glycolysis for the generation of ATP, the pentose phosphate pathway for NADPH regeneration, and the purine salvage pathway for maintaining adequate nucleotide concentrations. Many of these rate-limiting enzymes are pH sensitive, including hexokinase ( HK1 ), phosphofructokinase isozymes ( PFKL , PFKM , PFKP )[102], and G6PD . The product of glycolysis in RBCs is lactate [31], which exists in equilibrium with lactic acid at physiological pH.…”
Section: Resultsmentioning
confidence: 99%
“…At low oxygen saturation, the bound glycolytic enzymes are outcompeted by deoxyhemoglobin and released. The release of glycolytic enzymes to the cytosol corresponds to an increase in the activity of these rate-limiting enzymes the glycolytic pathway[102,106,107], consequently forming an intricate feedback loop in which oxygen transport and delivery is finely regulated through RBC metabolic demands [108].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…ATP (and other indices of glycolytic activity such as lactate and hypoxanthine) in turn associated significantly with hemolytic propensity ex vivo and after RBC transfusion in critically ill patients. PKLR (encoding PK in the liver and RBCs) was among the genes for which metabolite quantitative trait loci associated significantly with glycolysis, suggesting a druggable target for potential intervention ( Nemkov et al, 2024 ).…”
Section: Red Blood Cell Storagementioning
confidence: 99%
“…Large studies of the degree of post-transfusion recovery of RBCs in recipients have revealed substantial variability from donor to donor, and high reproducibility of post-transfusion recovery (PTR) of RBCs from a given donor, consistent with the importance of heritable traits governing this essential measure of transfusion effectiveness. The variability in PTR is clearly linked to variable donor genetics and metabolomes ( Nemkov et al, 2024 ).…”
Section: Red Blood Cell Storagementioning
confidence: 99%